1979
DOI: 10.1152/ajpheart.1979.236.2.h345
|View full text |Cite
|
Sign up to set email alerts
|

Thermal quantification of region myocardial perfusion and heat generation

Abstract: A technique for experimental determination of regional myocardial blood flow and heat generation has been developed, based on a heat-clearance method. This method allows repetitive and frequent measurements of regional blood flow without necessity for biopsy or microspheres. Testing was performed on a pedicle preparation, an intact segment of left ventricular myocardium dependent on a single diagonal coronary artery and situated in situ in the left ventricular free wall. Total blood flow to the pedicle was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1979;Shitzer & Eberhart, 1979). This approach, based upon analysis of the kinetics of local temperature change following temperature perturbation, has been analysed theoretically by Shitzer & Eberhart (1979) and verified experimentally (Hernandez et a!. 1979 Thus, all measurements must be expressed in terms of percentage change from control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1979;Shitzer & Eberhart, 1979). This approach, based upon analysis of the kinetics of local temperature change following temperature perturbation, has been analysed theoretically by Shitzer & Eberhart (1979) and verified experimentally (Hernandez et a!. 1979 Thus, all measurements must be expressed in terms of percentage change from control.…”
Section: Discussionmentioning
confidence: 99%
“…The same principle has been applied in the dog kidney in which thermal conductivity was measured after heating a small adjacent area (Muller-Schauenburg et al 1975;Olshausen et al 1976). Similarly, the principle of heat clearance has recently been applied to quantitative measurement of regional tissue blood flow in the myocardium (Hernandez et a!. 1979;Shitzer & Eberhart, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbs (1967) has measured metabolic heat directly in the papillary muscle, and reported values which were an order of magnitude lower than the heat changes measured as a function of coronary blood supply. Similarly, Hernandez, Hoffman, Fabian, Siegel & Eberhart (1979) showed that heat changes produced by changes in local blood flow are much greater than those produced by metabolic heat.…”
Section: Discussionmentioning
confidence: 99%